Lead induced changes in biomarkers and proteome map of Chicory (Cichorium intybus L.) - Malik, Bisma; Pirzadah, Tanveer Bilal (Current Botany, 2020)
Lead (Pb) toxicity is a serious environmental problem as it affects the food production by interfering plant growth and development, thus declines the production yield. In the present research work, Cichorium intybus L. plants were subjected to different concentrations of Pb (0, 100, 200 and 300µM) upto 46days to determine the oxidative stress. The length of root and shoot, accumulation of biomass were estimated along with the changes in biomarkers (H2O2 and TBARS). Further proteomic analysis of chicory leaves (46days old) at 300µM Pb concentration was done to identify the proteins of interest. The root growth increased significantly in a concentration-dependent manner however; shoot growth, biomass accumulation declined significantly with Pb stress compared to control. Changes in biomarkers (H2O2 and TBARS) content elevated with the increment in the concentration of metal treatment but exhibited a gradual decline at 300µM Pb treatment.. Proteomics data of 46days old chicory plants under 300 µM Pb stress analyzed by PDQuest software detected approximately 168 protein spots on each gel and 81 spots were differentially expressed in which 16 were up-regulated and 13 were down-regulated. The present study suggested that chicory possess a strong antioxidative defense system to combat Pb stress and thus could be explored for cultivation in Pb contaminated soils.